The importance of pollination type (self or cross) in two self-compatible almond cultivars: Francolí and Guara - Martín I.; Rovira M. (XIV GREMPA Meeting on Pistachios and Almonds, 2010)
Type of pollination (self or cross-pollination), and their influence on nuts, in two self-compatible almond cultivars Francolí and Guara, growing in commercial orchards, was observed in 2006. One orchard with Glorieta and Masbovera cvs as pollinators of Francolí, and the second orchard with Ferraduel, Guara and Masbovera cvs. Four hundred fruits from Francolí and 160 from Guara were collected, characterized and put to germinate. Molecular markers (isozymes and SSRs) were applied to the seedlings to know the pollen source of each almond. Francolí nuts showed that self-pollination was higher (77 percent) than cross-pollination (23 percent). Type of pollination in Guara seeds seemed to be similar (61 percent self and 39 percent cross-pollination), although not all seedlings have been analyzed yet. So far, the results for both cultivars showed that the type of pollination has not affected the nut characters studied. Further observing years are planned.
14. GREMPA Meeting on Pistachios and Almonds, 2008/03/30-2008/04/04, Athens (Greece)